TRAINING PROGRAM FOR SPECIFIC ENDURANCE AND ITS EFFECTS ON BLOOD MEASUREMENTS, BLOOD PROTEINS, IMMUNE SYSTEM ACTIVITY, AND 800 M PERFORMANCE - Imad Faraj Badrawi Al-Khammas (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Middle-distance running, particularly the 800-meter event, demands a balance of aerobic and anaerobic capacities, alongside optimal physiological resilience. Training programs that incorporate special endurance exercises are considered essential for improving both performance and physiological adaptations, including immune system function. Objectives. This study aimed to examine the effects of a researcher-designed training program, based on special endurance exercises, on blood measurements, blood proteins, immune activity, and athletic achievement in the 800-meter race. Method. An experimental design with a one-group pre-test and post-test approach was employed. The training program was implemented over a defined period during 2024–2025. Pre- and post-measurements were conducted to evaluate immune variables, blood indicators, and 800-meter performance times. The training sessions were delivered under controlled conditions to minimize external influences and ensure standardized assessments. Results. The findings revealed significant improvements in immune system efficiency and favorable changes in blood-related variables after the intervention. Moreover, the training program contributed to enhanced performance, as shown by a substantial reduction in the 800-meter completion time. Conclusion. The specialized endurance training program effectively enhanced both physiological health indicators and athletic achievement in middle-distance runners.This study provides empirical evidence supporting the integration of structured special endurance exercises into training regimens to improve competitive performance while simultaneously promoting immune system function and overall athlete health.